Description of the octopunctata-group species of Protaphorura from China (Collembola: Onychiuridae) - Sun, Xin; Wu, Donghui; Gao, Meixiang (Zootaxa, 2013)
Protaphorura species of the octopunctata-group are recorded in China for the first time. Two new species, Protaphorura jiamusiensis sp. nov. and Protaphorura maoerensis sp. nov., and one species new to China, Protaphorura nutak, are reported. Protaphorura jiamusiensis sp. nov. is diagnosed mainly by the formula of pso on the body and subcoxae 1, the psx formula, the ratio of M/sp on Abd. V and the number of chaetae on Th. I–III sterna between the legs. Protaphorura maoerensis sp. nov. is similar to P. mongolica and P. sakatoi, but it can be easily distinguished from them by the dorsal pso formula.